Pancasila as Ideology and Characteristics Civic Education in Indonesia - Dewantara, Jagad Aditya; Suhendar, Ilham Fajar; Rosyid, Rum; Atmaja, Thomy Sastra (International Journal for Educational and Vocational Studies, 2019)
The role of Civic Education in its era of globalization is very necessary, given its very strategic position, especially for the formation of nation and character building. The purpose of this study is to prove that Civic Education in Indonesia is inseparable from the values of Pancasila. The literature method is used to get conclusions in proving that Pancasila is an ideology and characteristic of civic education in Indonesia. The results prove that Civic Education must be in accordance with Pancasila values in all aspects of citizenship learning. Therefore Pancasila is a characteristic of the State of Indonesia as a philosophical system animating all the concepts of Citizenship teachings and must be applied in the life of the nation and state.